IFPRI offer matches the GIZ-ATVET4W project’s demand - Gantoli, Geoffroy (2023)
Geoffroy Gantoli POLICY SEMINAR Introducing pro-WEAI complementary indicators for nutrition- sensitive agriculture and market inclusion projects MAR 2, 2023 - 9:00 TO 10:30AM EST